Advances in the biochemical diagnostics of primary aldosteronism: from immunoassays to steroidomics and proteomics - Szatko, Alicja; Toboła, Agata; Falhammar, Henrik; Zgliczyński, Wojciech; Glinicki, Piotr (Frontiers in Endocrinology, 2025)
Primary aldosteronism is the most common cause of secondary hypertension, yet most cases remain unrecognized and left without optimal treatment. The diagnostic inertia may be attributed to the lack of specific symptoms, insufficient awareness among physicians, still conflicting indications for screening for primary aldosteronism and first and foremost challenging diagnostics. This review describes the current challenges of biochemical diagnostics of primary aldosteronism, including screening, case confirmation and subtyping. It also discusses immunoassays widely used in assessment of suspected autonomous aldosterone secretion – recent advances in the field and limitations of the method in comparison to the gold standard - liquid chromatography –tandem mass spectrometry. The review focuses on the application of novel “omics” strategies in the diagnostics of primary aldosteronism. Steroidomics and proteomics offer a possibility to simultaneously assess steroids and protein/peptides on a large scale. This multianalyte approach in comparison to the selective quantification of a chosen compound has been proved useful in the diagnostics of primary aldosteronism. It also offers a unique insight into the individual characteristics, underlying mechanisms and even reflects the genetic alterations of primary aldosteronism cases. The “omics” techniques are associated with large amounts of generated data, the interpretation of which may be troublesome and often necessitates the use of artificial intelligence. The novel advances in the biochemical diagnostics of primary aldosteronism, including “omics” techniques, presented in this review may help to address the most emerging problems, increase the number of diagnosed patients and facilitate the choice of an optimal treatment.